Enhancing engine performance and reducing carbon emissions using medical syringe waste and compressed natural gas in dual-fuel operations - Sathish. T; Saravanan. R (Results in Engineering)
Medical field development supports the healthy life of human life. On the other side, it produces higher environmental pollution by their wastes. Among these medical wastes syringe wastes can be used to produce the alternate fuel by pyrolysis as 71 % of yield. This Medical syringe waste oil (MSWO) is used in the 5.2 KW CI engine and produces higher emissions and poor performance. Therefore, MSWO blends with diesel at 80 %:20 % and 20 %:80 % ratio by volume. Further improvement is dual fuel mode operation examined with compressed natural gas (CNG) by 10 % and 20 % of energy share with the blends at different loads. Higher diesel contributed to the MSWO blend, which has improved performance and reduced emission compared to MSWO without the blend. The CNG used dual fuel mode operation to improve the combustion quality by the premixed charge. MSWO of 20 %, diesel of 80 % supplied as a main fuel and the 20 % of CNG port fuel supplied dual fuel operation has 11.94 % higher brake thermal efficiency, 29.4 % lesser CO emission, 26.58 % lesser UHC emission, 26.18 % lesser soot emission, and 9.36 % higher NOx emission than diesel at full load. Therefore, this combination of MSWO blend is recommended with CNG dual-fuelled operation for improved performance and reduced emission than diesel. Higher use of this oil use in engines will reduce the medical syringe wastes in the environment.